INCREASING STUDENT LEARNING OUTCOMES THROUGH THE APPLICATION OF THE DISCOVERY LEARNING MODEL ON MECHANICAL WAVES IN CLASS XI MIPA 3 SMA NEGERI 1 BANGSAL MOJOKERTO - Nur Mukhlas (Jurnal Scientia, 2022)
Specifically, based on observations and initial reflections, it is shown that class XI MIPA 3 at SMA Negeri Bangsal is a class with low learning motivation. In these classes, students tend to pay less attention to lessons, the learning outcomes obtained also do not meet the Minimum Completeness Criteria. The results of the previous material test completeness only reached 66.67% or only 22 students out of 33 students completed. Based on this, research was carried out with the aim of knowing the improvement of student learning outcomes in mechanical wave material through discovery learning learning models at SMA Negeri 1 Bangsal Mojokerto Class XI MIPA 3 semester 2 of the 2017/2018 academic year. This research is a classroom action research conducted in March – April 2018 involving 33 students of class XI MIPA 3 academic year 2017/2018. This research was conducted in two cycles, each cycle consisting of 4 (four) stages, namely planning, implementation, observation, and reflection. Based on the results of research and reflection, it can be concluded that the implementation of the discovery learning model is more effective. The implementation of discovery learning learning models can also improve and complete student learning outcomes, this is evidenced by the increase in classical completeness from 84.85% in the first cycle to 90.9% in the second cycle. In addition, through the discovery learning model, student activities become more active, and are able to familiarize scientific behavior.